(ARTIKEL INI DICABUT-RETRACTED) Mesopotamia dan Mesir Kuno: Awal Peradaban Dunia (ARTIKEL INI DICABUT-RETRACTED) - Nuraini A Manan (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
The existence of civilization cannot be separated from the existence of human beings. Mesopotamia and Ancient Egypt were the centers of the oldest civilization in the world. Both Mesopotamia and Ancient Egypt had typical characteristics. Mesopotamian civilization was more non-physical compared to Egypt. Sciences were emphasized more in Mesopotamia, while Egypt emphasized religious aspects. Political systems in both areas were almost the same, that is, absolutism and considered the king as god. Mesopotamia was more humanist than Egypt. The effectiveness of both civilizations was determined much by political power and economy.THIS ARTICLE IS RETRACTED